Islamic economic perspective on balancing growth and equity: A quantitative analysis of inflation and investment in ASEAN economies - Mahmudin, Rizal; Madnasir; Sisdianto, Ersi (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study examines the interplay between inflation, investment, unemployment, and poverty and their collective impact on sustainable economic growth within the ASEAN region over the period from 2018 to 2022. Employing a quantitative approach with panel data analysis, the research focuses on five developing ASEAN countries. The analysis reveals that both inflation and unemployment significantly influence sustainable economic growth, while investment and poverty also play critical roles in shaping economic outcomes. From an Islamic economic perspective, the findings highlight the necessity of balancing material growth with spiritual values, environmental stewardship, justice, ethics, and community empowerment. This study underscores that economic growth should not only focus on immediate gains but must also prioritize long-term sustainability, ensuring that development benefits both current and future generations. The implications of this research offer valuable insights for policymakers in developing holistic strategies that align with Islamic economic principles, promoting equitable and sustainable growth.